2015
DOI: 10.1016/j.celrep.2015.08.069
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR Enhances the Androgen-Receptor-Mediated Transcriptional Program and Drives Castration-Resistant Prostate Cancer

Abstract: SUMMARY Understanding the mechanisms of androgen receptor (AR) activation in the milieu of low androgen is critical to effective treatment of castration-resistant prostate cancer (CRPC). Here, we report HOTAIR as an androgen-repressed lncRNA, and, as such, it is markedly upregulated following androgen deprivation therapies and in CRPC. We further demonstrate a distinct mode of lncRNA-mediated gene regulation, wherein HOTAIR binds to the AR protein to block its interaction with the E3 ubiquitin ligase MDM2, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
249
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(262 citation statements)
references
References 32 publications
11
249
1
1
Order By: Relevance
“…http://dx.doi.org/10.1101/376277 doi: bioRxiv preprint first posted online Jul. 24, 2018; or activation by modulating their activity (52,54). For example, MALAT1, a known nuclear lncRNA interacts with EZH2, facilitates its occupancy and the H3K27me3 activity on the PRC2 target genes (18), in corroboration to this, we also found that MALAT1 interacts with EZH2 and might facilitate its recruitment on miRNAs regulatory regions.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…http://dx.doi.org/10.1101/376277 doi: bioRxiv preprint first posted online Jul. 24, 2018; or activation by modulating their activity (52,54). For example, MALAT1, a known nuclear lncRNA interacts with EZH2, facilitates its occupancy and the H3K27me3 activity on the PRC2 target genes (18), in corroboration to this, we also found that MALAT1 interacts with EZH2 and might facilitate its recruitment on miRNAs regulatory regions.…”
Section: Discussionsupporting
confidence: 71%
“…Numerous lncRNAs have been reported to be dysregulated in prostate cancer (51,52), for instance, PCGEM1 and PRNCR1 are highly expressed in aggressive PCa and enhance the AR-mediated gene activation program (53). Furthermore, MALAT1 renders cell cycle arrest in G1/S transition and mitotic phase by modulating the expression of E2F1 and B-MYB (25).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for such migration and the cell growth-promoting ability of SOCS2-AS1 may be the modulation of AR signaling by SOCS2-AS1. As in several lncRNAs such as HOTAIR (22) and PCGEM1 (58), Our ChIP analysis indicated that SOCS2-AS1 may be involved in the modification of AR for recruiting epigenetic modifiers without changing the AR protein level or binding to genome. However, TNFSF10 is up-regulated even in the absence of DHT by SOCS2-AS1 knockdown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCAT-1 was characterized as a novel prostate-specific lncRNA, regulator of cell proliferation, and target of the polycomb repressive complex 2 (PRC2) (15). HOTAIR RNA binds to AR protein to block the interaction with the E3 ubiquitin ligase MDM2, thereby preventing protein degradation and AR activation (22).…”
mentioning
confidence: 99%
“…This suggests that some cell-free lncRNAs carry regulatory signals involved in pathological conditions such as tumor occurrence, invasion, and metastasis, and might thus be potential biomarkers for cancer [24-26]. Indeed, researchers have identified three circulating lncRNAs, Linc00152, CFLAR-AS1, and POU3F3, as potential biomarkers for predicting the development of human esophageal squamous cell carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%